Anthropology, Feminism and the Postmodern Context - Boddy, Janice (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1991)
In a recent article, Marylin Strathern (1987) suggested that feminism and anthropology exist in fundamental tension, stemming from the different ways they constitute their subject matter as “other,” and from their divergent conceptualizations of experience. Whereas anthropology attempts, if incompletely, to bridge the gap between self and other, the authority of feminism resides in the maintenance of that gap – here, between women and men. However I argue that not all feminist writing can be seen in this light. In the postmodern situation feminism and anthropology clearly intersect, for both employ forms of deconstructive practice to expose and possibly critique the contexts in which “others” (including the writers themselves) are embedded.